Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Guru SD Al – Muttaqin “Fullday School” Kota Tasikmalaya - Syahra Aliya; Barin Barlian; Ai Kusmiyati Asyiah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to determine how much influence Competence and Work Discipline have on Teacher Performance at SD Al Muttaqin "Fullday School" Tasikmalaya City. The method used in this research is quantitative with a survey approach. With a research sample of 44 people as respondents to SD Al Muttaqin "Fullday School" Tasikmalaya City based on 44 known population data. The data used is using primary data. Data collection techniques used are observation, interviews, and questionnaires. The analytical tool used in this study is multiple linear regression using the SPSS version.25 support application, multiple correlation, F test, T test, and the coefficient of determination. The results showed that partially competence and work discipline had a significant effect on the performance of SD Al-Muttaqin "Fullday School" teachers. Simultaneously the effect of competence and work discipline on teacher performance is 87.6%. The influence of a strong variable is competence with a coefficient of 45.83%. While the coefficient of work discipline is 32.83%